(untitled) (Altre Modernità, 2019)
This contribution deals with Kiezdeutsch, a form of youth slang spoken in multilingual and multi-ethnic urban settings in Germany. Based on three works by German scholars published in the past few years the linguistic features of Kiezdeutsch are described and the issues of its sociolinguistic status and of its origin are discussed. Then, the role played by Kiezdeutsch in present day German society is scrutinized relying on the dichotomy ‘community vs. migrancy’.